‘Wholly artificial arrangements’ and the erosion of national tax bases : An analysis of CJEU case law on direct taxation - Wideman, Robin (My University, 2025)
This thesis examines the concept of ‘wholly artificial arrangements’ as developed by the Court of Justice of the European Union in its case law on direct taxation. The thesis aims to define what the concept entails, its relation to the issue of erosion of the Member States’ national tax bases and how the concept might be developed. The thesis employs the doctrinal research methodology, focusing on the jurisprudence of the Court and aided by relevant peer-reviewed academic literature. The fundamental freedoms afford opportunities to avoid national taxes by moving profits to low-tax jurisdictions by triggering the freedoms via artificial cross-border arrangements. The Court plays a pivotal role in developing the law in the field of direct taxation due to low legislative harmonization. In so doing it has to strike a careful balance between tax base protection and the internal market freedoms. The concept of ‘wholly artificial arrangements’ is deeply embedded in the prohibition of abuse of Union law, which in turn is a central construct in combating tax evasion and by extension the erosion of national tax bases. According to this thesis an arrangement is deemed ‘wholly artificial’ if it lacks ‘economic reality’ and has the aim of avoiding taxes. The ‘economic reality’ of an establishment is assessed by examining the physical existence of a subsidiary and whether the arrangement corresponds to market terms. The definition of artificiality is broader in the realm of free movement of capital, requiring tax evasion to be one of, but not the only aim of the arrangement. The thesis recommends a shift away from emphasizing physical existence and more towards assessing the conducted activity, which would correspond better to a modern business environment. Redefining the concept to more flexibly account for situations of substantial but not quite ‘whole’ artificiality would better serve the interest of tax base protection.
Keywords: abuse of law, direct taxation, fundamental freedoms, tax base erosion, the Court of Justice of the European Union, wholly artificial arrangements